Sustainability in engineering programs in UMinho - Colombo, Ciliana Regina (2016)
Rethink the interventions, human practices and their effects on the natural environment, for the preservation of life and biodiversity, threatened by the capitalist model of production, consumption and disposal, becomes each day more indispensable and then the understanding of the environmental crisis is gaining space in all segments of society. This understanding is increasingly founded on theoretical and epistemological assumptions, so that considering the role of universities as knowledge building space and other duties and responsibilities towards society, this authors papers understand fundamental the insertion of the environmental approach (greening) in its various fronts (education, research, extension and management). Following the line of several researches about the subject, as well as from research groups in Brazil and in Portugal to which authors are affiliated, this paper aims to identify how the issue of sustainability is taught in the various UMinho engineering programs. This study is part of a broader research, and thus it is limited to teaching, within the engineering scope of this university. It is, therefore, a case study, carried out by a documental research that aims to identify at the UMinho engineering programs that incorporate sustainability concepts into their curricula and, within these programs, identify the courses that possibly work aspects of sustainability and how they work these, particularly, if they use PBL to do this. Also, it is intended to find out about other activities that work the theme and that somehow subsidize the education for a more complete approach to sustainability through research and extension. The study, thus, provides an overview of the greening of engineering courses UMinho, and highlights those working the theme according to a systemic approach, problematizing, practical and integrative that already it was found in several studies be the most suitable to make professionals focused on sustainability.